2019
DOI: 10.5539/mas.v13n11p54
|View full text |Cite
|
Sign up to set email alerts
|

Growing Wheat and Vegetable Crops on Medium Composed of Olive Mill Wastewater, Pomace, and Limestone

Abstract: The main objective of this project is to develop sustainable method of innovative agriculture practices that relies on reducing the liquid and solid waste generated from olive mill and limestone slurry by-product from factories in Palestine. The second aim is to use these waste by-products in a proper ratio mixture and their feasibility in the agricultural use for optimal and best conditions. The overall output is the implementation of applied research on wheat crop and solanaceous vegetables including tomato … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Indeed, the high salinity level could lead to a reduction of the plant's water uptake capacity by reducing the growth rate, the number of leaves, and roots, with time [Hasanuzzaman and al., 2013]. According to Houshia and al, (2019), the high level of acidity will be able to lead to reduced growth in tomatoes [Houshia and al., 2019]. Recent studies have shown that the irrigation of tomato plants by OMW did not cause toxicity symptoms in fruits and plants [de los Santos and al., 2021; El-Bassi and al., 2021].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the high salinity level could lead to a reduction of the plant's water uptake capacity by reducing the growth rate, the number of leaves, and roots, with time [Hasanuzzaman and al., 2013]. According to Houshia and al, (2019), the high level of acidity will be able to lead to reduced growth in tomatoes [Houshia and al., 2019]. Recent studies have shown that the irrigation of tomato plants by OMW did not cause toxicity symptoms in fruits and plants [de los Santos and al., 2021; El-Bassi and al., 2021].…”
Section: Discussionmentioning
confidence: 99%